2022
DOI: 10.3390/ijms231911021
|View full text |Cite
|
Sign up to set email alerts
|

Dried Bilberry (Vaccinium myrtillus L.) Alleviates the Inflammation and Adverse Metabolic Effects Caused by a High-Fat Diet in a Mouse Model of Obesity

Abstract: Obesity is an increasing problem worldwide. It is often associated with co-morbidities such as type II diabetes, atherosclerotic diseases, and non-alcoholic fatty liver disease. The risk of these diseases can be lowered by relieving the systemic low-grade inflammation associated with obesity, even without noticeable weight loss. Bilberry is an anthocyanin-rich wild berry with known antioxidant and anti-inflammatory properties. In the present study, a high-fat-diet-induced mouse model of obesity was used to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Furthermore, the black raspberry extract inhibited the growth of the pathogenic genus Escherichia/Shigella and promoted beneficial bacteria, particularly Fusicatenibacter and Lachnoclostridium, in all microbiota sources [71]. These results validate the ability of anthocyanins to modulate gut microbiota composition and diversity, thereby contributing to potential health-promoting effects, including reducing insulin resistance, obesity, inflammation, and cardiovascular issues [101][102][103].…”
Section: Gut-microbiota Interaction and Colonic Metabolismmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, the black raspberry extract inhibited the growth of the pathogenic genus Escherichia/Shigella and promoted beneficial bacteria, particularly Fusicatenibacter and Lachnoclostridium, in all microbiota sources [71]. These results validate the ability of anthocyanins to modulate gut microbiota composition and diversity, thereby contributing to potential health-promoting effects, including reducing insulin resistance, obesity, inflammation, and cardiovascular issues [101][102][103].…”
Section: Gut-microbiota Interaction and Colonic Metabolismmentioning
confidence: 55%
“…Anthocyanins are widely studied for their ability to alleviate inflammation in animals, as depicted in Table 2, and are considered a potential therapeutic option for inflammatory bowel diseases. Anthocyanin-rich extracts from black rice [116], bilberry [103], blueberry [117], and Portuguese blueberry [118] all showed anti-inflammatory effects in mice with induced colitis. This is achieved by their ability to inhibit the pro-inflammatory cytokine secretions of TNF-α, IL-6, and IL-8, improving intestinal permeability, colonic MPO activity, and mRNA expression [119].…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 98%
“…In fact, the study shows a trend in the berry group of reduced insulin levels, although non-significant. Previous studies by us and others ( 83 , 84 ) have shown that a high dose (20%) of lingonberries and bilberries have shown protection against insulin resistance, body weight gain, body fat accumulation, and cholesterol levels in the same mouse strain fed a 45E% high-fat diet. The results on metabolic syndrome-related parameters have been especially promising with lingonberries, with some more mixed results for bilberries.…”
Section: Discussionmentioning
confidence: 76%
“…As a result of blueberry supplementation, serum insulin, glucose, and cholesterol concentrations were partly reduced, systemic and hepatic inflammation was suppressed, and undesirable changes in glucose/lipid metabolism were retarded. Consequently, blueberry supplementation appeared to support a healthier metabolic phenotype during obesity development [103].…”
Section: Diabetologymentioning
confidence: 99%